Faktor-Faktor Penyebab Terjadinya Alih Fungsi Lahan Sawah Di Provinsi Lampung - Robet Asnawi; Ratna Wylis Arief; Slameto Slameto (JURNAL WACANA PERTANIAN, 2022)
Increasing economic growth and population has led to increase land needed, including paddy fields which have been converted into settlements, industry, roads and non-rice farming. This study was conducted in 6 regency at Lampung Province, from June to November 2019. The study aims to determine factors cause land conversion paddy fields in Lampung Province. This research was conducted using survey method with total 240 respondents. The primary data collected were characteristics of farmers, ownership of paddy fields assets, land tenure, lowland rice farming costs, farmer's income, and factors that caused land conversion. Secondary data collected in the form of 2014-2018 time series data were ​​rice fields area, planted area, production, and productivity, and data of ​​LP2B per regency/city, conversion of paddy fields area, and new rice fields. The results show that the planted area of ​​lowland rice in Lampung Province experienced an average growth of 11.7%. In general, its was increased in the standard of ​​rice fields area by 2.6%, while its was decrease in the standard of ​​rice fields area in Bandar Lampung City by 1.2%, South Lampung Regency 0.3% and Pringsewu 1.1%. Total new paddy fields area in Lampung Province in last 5 years were 21,550 ha such as in Mesuji District (10,185 ha), Tulang Bawang (6,671 ha), and Way Kanan (2,250 ha). The conversion of functions of paddy fields in the 6 regencies/cities in the study locations average of 18.1%, most of which were converted to toll roads, settlements, factories, rubber, cassava and citrus farming. The factors that have a significant effect on converting paddy fields to non-rice fields were age of farmer, education level, number of family members, educational costs, and total value of household assets, while the total household income, number of working children and farm productivity were not significant effect.